miR-1260b Activates Wnt Signaling by Targeting Secreted Frizzled-Related Protein 1 to Regulate Taxane Resistance in Lung Adenocarcinoma - Ren, Jin; Wang, Deqiang; Huang, Hanpeng; Li, Xiaoqin; Zhuang, Xiufen; Li, Jian (Frontiers in Oncology, 2020)
Objectives: MicroRNAs (miRNAs) have been demonstrated to contribute to carcinogenesis; however, their association with tumor chemoresistance is not fully understood. In this study we aimed to investigate the molecular mechanisms involved in resistance to taxane-based chemotherapy in lung adenocarcinoma (LAD). Methods: We established paclitaxel-resistant A549 cells (A549/PTX) and docetaxel-resistant H1299 cells (H1299/DTX). In order to hit the mark, we employed multiple methods including microarray analysis, qRT-PCR, western blotting analysis, loss/gain-of-function analysis, luciferase assays, drug sensitivity assays, animal experiment, wound-healing assay and invasion assay. Results: Based on miRNA microarray analysis, we found that miR-1260b was significantly upregulated in taxane-resistant cells as compared to parental cells. Suppression of miR-1260b reversed the chemoresistance of human LAD cells to taxanes both in vitro and in vivo, whereas ectopic miR-1260b expression decreased the sensitivity of parental LAD cell lines to taxanes. Bioinformatics analysis and a luciferase reporter assay revealed that secreted frizzled-related protein 1 (SFRP1) is a direct target of miR-1260b, and downregulation of miR-1260b expression inactivated the Wnt signaling pathway and reversed the epithelial-mesenchymal transition (EMT) phenotype of taxane-resistant LAD cells. In clinical tumor tissue samples, high miR-1260b expression was detected in tumors of nonresponding patients treated with taxane-based chemotherapy and was associated with low SFRP1 expression and poor prognosis. Conclusions: Our findings reveal that targeting of the miR-1260b/SFRP1/Wnt signaling axis might provide a novel strategy for overcoming chemotherapy resistance in LAD.